Constitutive Activation of NF-κB Pathway in Hematopoietic Stem Cells Causes Loss of Quiescence and Deregulated Transcription Factor Networks - Nakagawa, Masahiro Marshall; Chen, Huanwen; Rathinam, Chozha Vendan (Frontiers in Cell and Developmental Biology, 2018)
Identifying physiological roles of specific signaling pathways that regulate Hematopoietic Stem Cell (HSC) functions may lead to new treatment strategies and therapeutic interventions for hematologic disorders. Here, we provide genetic evidence that constitutive activation of NF-kB in hematopoietic stem cells (HSCs) results in reduced pool size, repopulation capacities and quiescence of HSCs. Global transcriptional profiling and bioinformatics studies identified loss of 'stemness' and 'quiescence' signatures in HSCs with deregulated NF-kB activation. In particular, Gene Set Enrichment Analysis (GSEA) identified upregulation of Cyclin dependent kinase- ccnd1 and down regulation of Cyclin dependent kinase inhibitor (CDKI) p57kip2. Interestingly, constitutive activation of NF-kB is sufficient to alter the regulatory circuits of transcription factors (TFs) that are critical to HSC self-renewal and functions. Molecular studies identified Junb, as one of the direct targets of NF-kB in hematopoietic cells. In essence, these studies demonstrate that aberrant activation of NF-kB signals impairs HSC quiescence and functions and alters the 'transcription factor networks' in HSCs.